New Order Era Children’s Literary Mode of Production in Indonesia: Interaction and Articulation - Sari, Norma Atika; Salam, Aprinus (Angstrom Centre of Education, 2025)
The New Order era was the golden age of children's literary production in Indonesia, both in the form of books or magazines. The 1973 Presidential Instruction Book Project (Inpres) was one of the government programs that made the terms of quantity it has skyrocketed. In addition, the trend of magazine publishing as a result of press industrialization also confirmed this claim. The question that then arises is: what are the characteristics of the children's literary mode of production and how is the structure of interaction and articulation with other constituents? The basic premise of the hypothesis in this research is that children's literature is not a genre that is innocent and emerges organically. By using qualitative descriptive method and applying Eagletonian materialistic critical theory, researchers found that there are two children's literary modes of production; (1) the mode under the state patronage which is the dominant ones, and (2) the subordinate mode of production in the private sector. The interaction between both that historically coexisted was synchronic and negotiative. Both articulate the ideology of New Order developmentalism which is identical to poverty alleviation through “hard work” using the aesthetics of realist texts. In the subordinate mode of production, hidden social criticism is found where the state is not present in the efforts to eradicate poverty represented by the characters in the text. The New Order's control mechanism in determining children's literary mode of production was through Issuance Permit (SIT).